2010
DOI: 10.2147/ijn.s10443
|View full text |Cite
|
Sign up to set email alerts
|

Human serum albumin nanoparticles as an efficient noscapine drug delivery system for potential use in breast cancer: preparation and in vitro analysis

Abstract: Drug delivery systems such as nanoparticles can provide enhanced efficacy for anticancer agents. Noscapine, a widely used cough suppressant for decades has recently been shown to cause significant inhibition and regression of tumor volumes without any detectable toxicity in cells or tissues. Nanoparticles made of human serum albumin (HSA) represent promising strategy for targeted drug delivery to tumor cells by enhancing the drug's bioavailability and distribution, and reducing the body's response towards drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(30 citation statements)
references
References 36 publications
1
28
1
Order By: Relevance
“…Bare HSA NPs exhibited sizes of ca. 110 nm, smaller than others previously reported [40, 41] thanks to the modified synthetic procedure followed (Fig. 1a).…”
Section: Resultscontrasting
confidence: 55%
“…Bare HSA NPs exhibited sizes of ca. 110 nm, smaller than others previously reported [40, 41] thanks to the modified synthetic procedure followed (Fig. 1a).…”
Section: Resultscontrasting
confidence: 55%
“…Nano-formulation delivery systems have been widely used because of their unique biocompatibility and stability [2]. Moreover, sufficient drug binding sites are contained in human serum albumin (HSA) molecules, endowing albumin NPs with a high drug-loading capacity [3,4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that the noscapine NPs were significantly better than free noscapine in reducing the cell viability of SK-BR-3 (Sebak et al, 2010). …”
Section: Nanoparticlesmentioning
confidence: 99%